California's Mental Health Services Act and Mortality Due to Suicide, Homicide, and Acute Effects of Alcohol: A Synthetic Control Application. Issue 10 (21st April 2021) - Zimmerman, Scott C; Matthay, Ellicott C; Rudolph, Kara E; Goin, Dana E; Farkas, Kriszta; Rowe, Christopher L; Ahern, Jennifer
Abstract: California's Mental Health Services Act (MHSA) substantially expanded funding of county mental health services through a state tax, and led to broad prevention efforts and intensive services for individuals experiencing serious mental disorders. We estimated the associations between MHSA and mortality due to suicide, homicide, and acute effects of alcohol. Using annual cause-specific mortality data for each US state and the District of Columbia from 1976–2015, we used a generalization of the quasi-experimental synthetic control method to predict California's mortality rate for each outcome in the absence of MHSA using a weighted combination of comparison states. We calculated the association between MHSA and each outcome as the absolute difference and percentage difference between California's observed and predicted average annual rates over the postintervention years (2007–2015). MHSA was associated with modest decreases in average annual rates of homicide (−0.81/100, 000 persons, corresponding to a 13% reduction) and mortality from acute alcohol effects (−0.35/100, 000 persons, corresponding to a 12% reduction). Placebo test inference suggested that the associations were unlikely to be due to chance. MHSA was not associated with suicide. Protective associations with mortality due to homicide and acute alcohol effects provide evidence for modest health benefits of MHSA at the population level.